First Nations education policy in Canada : progress or gridlock? - Paquette, Jerald E., 1946-; Fallon, Gérald (University of Toronto Press, 2010)
Offering a sorely needed fresh perspective on an issue vital to the community, First Nations Education Policy in Canada is grounds for critical reflection not only on education but on the future of Aboriginal self-determination.